Klausa Michaela Meyer-Abicha teoria odpowiedzialności - Paulina Selmaj-Pomaska (Studia Ecologiae et Bioethicae)
This article presents the K. M. Meyer-Abich theory of responsibility. It discusses the essence of human responsibility as it arises especially at times of ecological crises. The circle of responsibility should be so wide as to prevent anything from existing merely for the sake of human needs. K. M. Meyer-Abich’s theory focuses on eight periods of human development, which correspond to eight circles of responsibility referring to eight ethical conceptions. Throughout human history, we can see how the scope of responsibility has been increasing to fall upon more and more entities. The extension of the circle of responsibility moved from the individual to include family and friends, the nation, all peoples of the world, and humanity as a whole, including future generations. The final step was to look beyond the boundaries of humanity to include all life forms.